2021
DOI: 10.1037/xhp0000936
|View full text |Cite
|
Sign up to set email alerts
|

Attentional guidance by irrelevant features depends on their successful encoding into working memory.

Abstract: Attentional selection is guided by templates of the target in working memory. It has been proposed that attentional templates integrate target features (e.g., purple chair) to guide attention in an object-based fashion. Alternatively, it may be that attentional templates are established for each target feature individually (e.g., purple and chair). To provide support for the latter account, we used a task where participants memorized a target shape while ignoring an irrelevant color. In the combined condition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Presumably, the amplitude of Ppc may reflects not only the saliency of target stimuli in the visual field but also the relative saliency between the distractor and the target. Nevertheless, recently work by Kerzel & Cong (2021) have found that with closer spatial proximity of distractors to the target location, comes smaller Ppc amplitude to the lateral singleton distractor, suggesting that it does reflect attentional processing to some degree. On the other hand, the Ppc was equally present for their singleton target and singleton distractor, suggesting that the Ppc reflects some task independent processes, as in the present study.…”
Section: Experiments 2: Attentional Capture and Suppression Of The Ab...mentioning
confidence: 93%
See 1 more Smart Citation
“…Presumably, the amplitude of Ppc may reflects not only the saliency of target stimuli in the visual field but also the relative saliency between the distractor and the target. Nevertheless, recently work by Kerzel & Cong (2021) have found that with closer spatial proximity of distractors to the target location, comes smaller Ppc amplitude to the lateral singleton distractor, suggesting that it does reflect attentional processing to some degree. On the other hand, the Ppc was equally present for their singleton target and singleton distractor, suggesting that the Ppc reflects some task independent processes, as in the present study.…”
Section: Experiments 2: Attentional Capture and Suppression Of The Ab...mentioning
confidence: 93%
“…On the other hand, the Ppc was equally present for their singleton target and singleton distractor, suggesting that the Ppc reflects some task independent processes, as in the present study. Conclusions from Kerzel & Huynh Cong (2021) suggest that Ppc is simultaneously affected by task demands and saliency, and it is difficult to decide “ whether the Ppc reflects bottom–up or top– down effects .” Future work may be needed to elucidate the nature of Ppc component, and to investigate this interesting analogy between abrupt onsets and color singletons.…”
Section: Experiments 2: Attentional Capture and Suppression Of The Ab...mentioning
confidence: 99%